A Showcase of Bench-to-Bedside Regenerative Medicine at the 2010 ASNTR. (2nd October 2011) - Eve Eve, David J. David J.; Borlongan Borlongan, Cesar V. Cesar V.; Sanberg Sanberg, Paul R. Paul R.
Abstract : Insight into the expanding themes of regenerative medicine is provided by the American Society for Neural Therapy and Repair's annual meeting. The 17th meeting covered a wide range of neurodegenerative disorders, exploring methods to elucidate the currently unknown mechanisms behind the disorders, as well as possible treatments ranging from the use of growth factors, gene therapy to cell transplantation. The importance of growth factors, both as a contributing factor to a disease and as a possible treatment either solo, or as a consequence of, or in conjunction with, stem cell therapy, was highlighted. The potential for viral vectors was also explored either for cells prior to transplantation or as a direct treatment regime into the brain itself. Identification of biomarkers that would allow early detection of a disease is an important factor in our fight against disease. The ability to now perform whole genome analysis and biomolecular profiling provides hope that such markers could be identified which not only could identify this likely to suffer from a disorder but also could allow its progress to be monitored. A few preclinical and clinical cell transplantation trials were also introduced as potential areas of followup in the years to come.